Extraction optimization and characterization of collagen from chicken (gallus gallus domesticus) feet - Mokhtar, Nur Dhiya; Abdul Wahab, Widya; Hamdan, Nurul Ashima; Ab. Hadi, Hazrina; Abu Hassan, Muhamad Shafiq; Muhamad Bunnori, Noraslinda (Emirates Research Publishing Limited, Dignified Researchers Publications, 2017)
Previous studies have proved that chicken (Gallus gallus domesticus) feet can be one of the alternative sources of collagen. Besides of less risk of diseases and can be accepted by all religions, chicken feet also have high potential as a low cost of collagen source. Method of collagen extraction also plays an important role to obtain high percentage of end yield and the quality of collagen extracted. Optimization of collagen extraction was investigated by using three different soaking methods; 0.5 mol/L acetic acid with 0.1% bromelain, 0.5 mol/L acetic acid with 0.1% papain and 5% lactic acid for 36 hours. Various properties such as percentage of end yield, concentration of protein, pH, swelling percentage and SDS-PAGE patterns of collagen from chicken feet were evaluated in order to determine the best method of extraction and potential of bromelain to improve collagen extraction. No significant different (P > 0.05) have been recorded between all three methods used in this research which indicated that all treatments were not affected the pH, swelling percentage, percentage of end yield and concentration of extracted collagen. However, lactic acid method was showed the highest percentage of end yield and concentration with reading of 30.04% and 11.66 mg/ml respectively. Type I collagen has been determined as major component of collagen from chicken feet based on the result of SDS-PAGE. It also proven that bromelain has same potential as papain in order to improve protein digestion